2019
DOI: 10.5937/zz1904007t
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of diabetic ketoacidosis in children with newly diagnosed type 1 diabetes in Belgrade, Serbia: 10-year tertiary centre experience

Abstract: _______ 7 SAŽETAK Uvod/cilj: Dijabetesna ketoacidoza (DKA) je najznačajniji uzrok mortaliteta mladih sa tipom 1 dijabetesa melitusa (T1DM). Rezultati poslednjih istraživanja ukazuju na zabrinjavajuće visoku prevalenciju DKA u trenutku postavljanja dijagnoze T1DM kod mladih u Beogradu. Cilj ovog istraživanja bila je procena učestalosti DKA kod dece i adolescenata sa novootkrivenim T1DM tokom desetogodišnjeg perioda u tercijernom centru u Beogradu. Metode: Podaci su prikupljeni retrospektivnom pretragom medicins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…However, several studies have demonstrated and linked an increased incidence to multiple factors. For instance, younger age (9)(10)(11)(12)(13)(14) , uneducated parents, no relative with type1DM, residing in rural areas, and having low economic status were incriminated (9,12,13,15) .Nonetheless, not all the factors were explanatory (16) .…”
Section: Diabetic Ketoacidosis (Dka) Is a Common Complication Of Type...mentioning
confidence: 99%
“…However, several studies have demonstrated and linked an increased incidence to multiple factors. For instance, younger age (9)(10)(11)(12)(13)(14) , uneducated parents, no relative with type1DM, residing in rural areas, and having low economic status were incriminated (9,12,13,15) .Nonetheless, not all the factors were explanatory (16) .…”
Section: Diabetic Ketoacidosis (Dka) Is a Common Complication Of Type...mentioning
confidence: 99%
“…The life of these chronically ill chil-dren is specific, because management of T1DM is often complex and requires a high degree of patient and family involvement, decision making and regular glucose monitoring, injections of insulin and dose adjustments, carbohydrate estimation, therapy adjustments according to physical activity, emotional status, illness or infections, alcohol intake. Children with T1DM rate their own HRQOL as similar to their healthy peers [2][3][4][5], but they report disease specific problems, which are described in the literature [2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Previous studies highlighted that several factors are associated with poor metabolic control and worse HRQOL in children with T1DM such as: female gender, older adolescents, lower family income, social minority status, single parenthood, and lower level of adherence to treatment [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the National Diabetes Registry of Serbia for 2010 [21], 2014 [22], and 2017 [23], showed a large annual increase of newly diagnosed pediatric patients with T1DM, especially in those aged 5 -9 and 10 -14 years. Todorović et al found that during the ten-year period (from January 2007 to January 2017), 501 children with newly diagnosed T1DM were hospitalized at the Mother and Child Healthcare Institute of Serbia "Dr. Vukan Čupić" [6]. Therefore, the aim of the study was to assess the HRQOL in pediatric patients with T1DM and its association with sociodemographic (age, gender, and time since diagnosis in years) and clinical factors (glycosylated hemoglobin (HbA1c) levels and type of insulin therapy).…”
Section: Introductionmentioning
confidence: 99%